Relations between character strengths, school satisfaction, enjoyment of learning, academic self-efficacy, and school achievement: An examination of various aspects of positive schooling - Weber, Marco; Harzer, Claudia (Frontiers in Psychology, 2022)
This study is embedded in the theoretical framework of the engine model of positive schooling (Harzer et al., 2021). Accordingly, relations were investigated between students’ endogenous input variables (i.e., character strengths), process variables (i.e., school satisfaction, enjoyment of learning, and academic self-efficacy), and school achievement as an outcome variable. A sample of 300 students (between 10 and 17 years of age) completed web-based self-report measures for all key variables. Specific character strengths (e.g., love of learning, zest, hope, perseverance, perspective) were substantially positively related to school satisfaction, enjoyment of learning, academic self-efficacy, and/or school achievement. Exploratory mediation analyses supported the basic assumption that processes (i.e., school satisfaction, enjoyment of learning, academic self-efficacy) mediate the relations between character strengths as input variables and school achievement as an outcome variable. The findings underline the benefit of studying inputs, processes, and outcomes simultaneously to better understand the interplay among relevant variables in the context of positive schooling.